INTERAKSI SOSIAL ANTAR UMAT BERAGAMA DAN HUBUNGANYA TERHADAP PEMBENTUKAN AKHLAK SISWA DI SDN PANTILAKSANA - Asep Wildan (Program Studi Pendidikan Agama Islam, 2023)
Based on the preliminary results it was found that social interaction between religious communities and its relationship to the formation of student morals at SDN Pantilaksana. Issues that affect social interaction will have an impact on the formation of student morals, this is because the morals or habits themselves are influenced by the surrounding circumstances. The purpose of this study was to examine the relationship between social interaction and moral stance. This study uses a qualitative and quantitative approach. The results of this study indicate that it can be seen that social interactions between religious communities carried out by Muslim and non-Muslim students at Pantilaksana Elementary School tend to keep the distance between Muslim and non-Muslim students. In addition, the influence of social interaction between religious communities on the formation of morals is quite significant, this can be seen from how the formation of student morals is influenced by interaction, with a correlation coefficient of 0.589 with a significance value/p-value of 0.000, because the significance value is p < 0 .05, then Ho is rejected, meaning that there is a significant relationship between social interaction and one's morals. Findings related to the problem of the relationship between Social Interaction and Moral Establishment can have implications for reviewing policy improvements related to methods or learning that can increase social interaction between religious communities.